Errors and uncertainties of classical standing wave tube methods: SWR, TMTC and TMTM - Lanctot, Benoit; Panneton, Raymond; Atalla, Noureddine (Canadian Acoustics, 2000)
An analysis on three classical standing wave tube methods is presented to compare the precision and identifying the sensitive parameters. The studied methods are standard wave ratio (SWR), two microphone three calibration method (TMTC), two microphone transfer method (TMTM). A differential formulation is used to evaluate the errors and uncertainties on each of the methods. The porous test sample is modeled as an equivalent fluid using the Johnson-Champoux-Allard model. The results obtained for the 25 mm thick polyamide foam are described.